Man-made divinity in Sci-Fi : an exploration of Leto II Atreides in Frank Herbert’s God Emperor of Dune as reflection and reimagining of the christian trinity - Medalie, David (University of Pretoria, 2025)
Dissertation (MA (Creative Writing))--University of Pretoria, 2024.